ScratchAnalytics: Um Framework para Coleta e Análise de Interações em Projetos Scratch - Vaz Junior, Jorge Luis Nachtigall; Primo, Tiago Thompsen; Pernas, Ana Marilza (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2020: Anais do XXXI Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/cbie.sbie.2020.862, 2020)
Technological advancement and its impact on our lives gradually highlights the need to use technological resources in the educational environment. One of these resources is Scratch, a block programming tool, widely used in educational projects which aim to provide students with the teaching of programming from a creative and constructionist perspective. As a result, evaluations and validations become necessary, in order to provide more information on the impact generated by these projects. This work presents a proposal to facilitate the execution of these analyzes, through the implementation of a framework which automates the process of collecting and analyzing interactions made by students in Scratch.